Exercise intensity and load during mass-start stage races in professional road cycling - Padilla, S.; Mujika, I.; Orbananos, J.; Santisteban, J.; Angulo, F.; Goiriena, J. J. (Medicine & Science in Sports & Exercise, 2001)
Purpose: To evaluate exercise intensity and load during mass-start stages in professional road cycling, using competition heart rate (HR) recordings. Methods: Seventeen world-class cyclists performed an incremental laboratory test during which maximal power output (Wmax), maximal HR (HRmax), onset of blood lactate accumulation (OBLA), lactate threshold (LT), and a HR-power output relationship were assessed. An OBLAZONE (HROBLA +/- 3 beats.min-1) and an LTZONE (HRLT +/- 3 beats.min-1) were described. HR was monitored during 125 flat (<13 km uphill, < 800-m altitude change; FLAT), 99 semi-mountainous (13-35 km uphill, 800- to 2000-m altitude change; SEMO), and 86 high-mountain (>35 km uphill, > 2000-m altitude change; HIMO) stages. Each cyclist's competition power output was estimated from competition HR and individual HR-power output relationships. Competition training impulse (TRIMP) values and time spent at "easy," "moderate," and "hard" zones were estimated from HR and race duration. Results: Average %HRmax were 61 +/- 5%, 58 +/- 6%, and 51 +/- 7% in HIMO, SEMO, and FLAT stages, respectively, and estimated average power outputs were 246 +/- 44, 234 +/- 43, and 192 +/- 45 W. Competition HR values relative to HROBLA and HRLT were, respectively, 69 +/- 6, 79 +/- 9% in HIMO; 65 +/- 7, 74 +/- 11% in SEMO; and 57 +/- 8, 65 +/- 10% in FLAT stages. The amount of TRIMP in HIMO, SEMO, and FLAT stages were, respectively, 215 +/- 38, 172 +/- 31, and 156 +/- 31. Percentage time spent in the "moderate" and "hard" zones was highest in HIMO (22 +/- 14, 5 +/- 6%) followed by SEMO (15 +/- 13, 5 +/- 5%) and FLAT (9 +/- 7, 2 +/- 2%) stages. Conclusions: %HRmax, time distribution around HROBLA and HRLT, TRIMP, and load zones reflected the physiological demands of different mass-start cycling stage categories. The knowledge of these demands could be useful for planning precompetition training strategies.